Otomicroscopic and functional outcomes after cleft palate repair via Sommerlad intravelar veloplasty vs. modified Veau-Wardill-Kilner push-back. (November 2022) - Pollet, Naomi; Mennes, Tillo; Denys, Sam; Loos, Elke; Verhaert, Nicolas; Vander Poorten, Vincent; Hens, Greet
Abstract: Objective: We aim to compare the modified Veau-Wardill-Kilner push-back technique (VWK) and the Sommerlad intravelar veloplasty (Sommerlad IVVP) in terms of middle ear outcomes and oronasal fistulae frequency in three years old children. Methods: For this retrospective cohort study, data were collected and anonymized from consecutive patients with cleft palate (with or without cleft lip) who underwent surgery in our hospital between January 2008 and December 2018. Patients with syndromic diagnoses and patients who underwent surgical treatment elsewhere were excluded. We collected data from 101 children (202 ears) regarding middle ear complications at the age of three, including acute otitis media, middle ear effusion, tympanic membrane retraction, tympanic membrane perforation, tympanic membrane atelectasis and chronic otitis media with cholesteatoma. In addition, the presence of oronasal fistulae and the number of ventilation tubes received by the age of three were recorded. Results: The odds of children having a normal middle ear evaluation were 3.07 (95% Confidence interval (95%CI): [1.52, 6.12]; p < 0.05) times higher when children received Sommerlad IVVP compared to modified VWK. With 40.7% compared to 26.7%, a significantly higher incidence of middle ear effusion was present in the modified VWK group compared to Sommerlad IVVP (X 2 (1) = 4.38, p < 0.05). Furthermore, this group needed significantly more ventilation tube reinsertions (X 2 (2) = 12.22, p < 0.05) and was found to have a significantly higher incidence of oronasal fistula (53.5% vs. 17.2%, X 2 (1) = 14.75, p < 0.05). The latter was significantly associated with a higher need for ventilation tube reinsertion (X 2 (1) = 7.34, p < 0.05). Conclusion: This study shows superior middle ear outcomes and fewer oronasal fistulae after Sommerlad IVVP compared to modified Veau-Wardill-Kilner push-back at the age of three.